2023
DOI: 10.1111/jne.13249
|View full text |Cite
|
Sign up to set email alerts
|

European Neuroendocrine Tumor Society (ENETS) 2023 guidance paper for digestive neuroendocrine carcinoma

Abstract: This ENETS guidance paper, developed by a multidisciplinary working group, provides up‐to‐date and practical advice on the diagnosis and management of digestive neuroendocrine carcinoma, based on recent developments and study results. These recommendations aim to pave the road for more standardized care for our patients resulting in improved outcomes. Prognosis is generally poor for digestive NEC, most are advanced at diagnosis and median survival in metastatic disease is 11–12 months. Surgery can be of benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(101 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…The indication and the timing of surgery in MEN1-ZES are controversial, since it has been shown that patients with no imageable pancreatic tumour, who did not undergo surgery, have a good prognosis with 5-year survival rates around 90% and a 10 year survival rate of 54% in cases of disseminated distant metastases 72 [3]. One has to keep in mind that patients with MEN1-ZES always have small duodenal gastrinomas and almost never pancreatic gastrinomas, as demonstrated by pathological studies 60 [2, A].…”
Section: Men1-associated Gastrinomamentioning
confidence: 99%
See 1 more Smart Citation
“…The indication and the timing of surgery in MEN1-ZES are controversial, since it has been shown that patients with no imageable pancreatic tumour, who did not undergo surgery, have a good prognosis with 5-year survival rates around 90% and a 10 year survival rate of 54% in cases of disseminated distant metastases 72 [3]. One has to keep in mind that patients with MEN1-ZES always have small duodenal gastrinomas and almost never pancreatic gastrinomas, as demonstrated by pathological studies 60 [2, A].…”
Section: Men1-associated Gastrinomamentioning
confidence: 99%
“…The reader is referred to the ENETS 2023 guidance papers on non-functioning (NF-)Pan-NET and gastroduodenal NET for primary oncological treatment of pancreatic or duodenal NET, whereas management of poorly differentiated counterparts is discussed in the ENETS 2023 guidance paper for digestive NEC. 3 All recommendations in this guidance paper are graded according to the level of evidence (1)(2)(3)(4)(5) and strength of recommendation (A-D) (Table 2).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…For details please see text recommendation 2.8.1. 5 In cases with more than one risk factor even with normal imaging a careful discussion with the patient is necessary to decide on follow-up or oncological resection; risk factors are: size >1 cm, G > 1; L1; V1. eFTR, endoscopic full thickness resection; ESD, endoscopic submucosal dissection; FU, follow-up; mEMR, modified endoscopic mucosal resection (for example cap EMR); TAMIS, transanal minimallly invasive surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Anal canal neuroendocrine neoplasm (NEN) are usually NEC and often MiNEN with a squamous carcinoma component 4 . NEC and MINEN are discussed in a separate guidance paper 5 …”
Section: Introduction ‐ General Backgroundmentioning
confidence: 99%
See 1 more Smart Citation